2000
DOI: 10.1124/mol.58.6.1178
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Mutations of Protease-Activated Receptor-1 Result in Differential Activation by Thrombin and Thrombin Receptor Agonist Peptide

Abstract: The protease-activated thrombin receptor-1 (PAR-1) can be activated by both the tethered ligand exposed by thrombin cleavage and a synthetic peptide having the tethered ligand sequence (thrombin receptor agonist peptide or TRAP). We conducted a mutational analysis of extracellular residues of the receptor potentially involved in interaction with both the tethered ligand and the soluble peptide agonist. Agonist-stimulated calcium efflux in X. laevis oocytes or inositol phosphate accumulation in COS-7 cells was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
56
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(65 citation statements)
references
References 40 publications
(49 reference statements)
9
56
0
Order By: Relevance
“…7). In this regard, point and deletion mutation studies have highlighted the importance of the region comprising residues 83 Q to 89 S in NH 2 -terminal domain (43,45), suggesting that Der p 1 cleavage may involve, at the very least, 91 D-92 A. The ECL1 and 2 regions of PAR-1 also contain several Der p 1 cleavable sites, one of which namely, 258 L-259 N, is absent from PAR-2 and, if cleaved in PAR-1, would result in the direct loss of the essential 256 D (43) as well as, perhaps, altering the receptor conformation in the region of 260 E, a residue also thought to be important in the activation process (46).…”
Section: Discussionmentioning
confidence: 99%
“…7). In this regard, point and deletion mutation studies have highlighted the importance of the region comprising residues 83 Q to 89 S in NH 2 -terminal domain (43,45), suggesting that Der p 1 cleavage may involve, at the very least, 91 D-92 A. The ECL1 and 2 regions of PAR-1 also contain several Der p 1 cleavable sites, one of which namely, 258 L-259 N, is absent from PAR-2 and, if cleaved in PAR-1, would result in the direct loss of the essential 256 D (43) as well as, perhaps, altering the receptor conformation in the region of 260 E, a residue also thought to be important in the activation process (46).…”
Section: Discussionmentioning
confidence: 99%
“…Other differences have been observed when agonist peptides are used to activate PAR-1 (35)(36)(37)(38)(39)86). Some of the most compelling evidence has recently come forth from studies involving site-directed mutagenesis of the PAR-2 receptor.…”
Section: Figmentioning
confidence: 99%
“…Although these agonist peptides appear to elicit full responses, there is an emerging body of evidence which suggests that agonist peptides do not activate PAR-1 in the same manner as does thrombin (35)(36)(37)(38)(39). In addition, activation of PAR-1 by other proteases has shown differential signaling (40).…”
mentioning
confidence: 99%
“…Up to now, there is not structural information on the binding sites of these PAR1 antagonists to be used for structure-based design of new antagonists. However, recent mutagenesis studies on thrombin and/or PAR1 [34][35][36][37][38][39][40][41][42], X-ray of thrombin crystallized with diverse N-terminal fragments of PAR1 [43,44], and NMR studies on the (Ala 26 -Hse 103 ) N-terminal sequence of PAR1 [45] have shown that the first thrombin/PAR1 interaction is produced between the exosite I of thrombin and the hirudin-like sequence of PAR1 (K 51 YEPF 55 ), and that this first interaction is essential and determinant for high affinity. It seems that the hydrophobic residues F34, I82, L65 and Y76, and the basic residues R67 and R73, of the exosite I of thrombin are important for high affinity.…”
Section: Introductionmentioning
confidence: 99%